Treffinger Learning with Collaborative Assessment in Achievement of Creative Thinking Skill and Student Mathematical Disposition - Roby Sugiarto, Dede Retno; Kartono, Kartono; Mariani, Scolastika (Universitas Negeri Semarang, 2021)
The aim of this study is to determine the quality of Treffinger learning model with collaborative assessment on the achievement of students' creative thinking abilities and mathematical disposition. This study uses a mixed method with concurrent embedded design. Subject of this research is grade VIII students of SMP N 36 Semarang. Data collection on mathematical creative thinking ability was using tests, data collection mathematical disposition was using questionnaires and data collection on self-assessment and peer-assessment was using assessment sheets. The quality of learning was qualitatively valued from planning stage, performing stage and assessment stage. The result of mathematical creative thinking ability test was analyzed qualitatively using mean test, comprehensive test, mean deviation test and deviation proportion test, then an improvement test is performed on the selected student. Result of this research shows Treffinger learning model with collaborative assessment on the achievement of students' creative thinking abilities and mathematical dispositions is considered well both qualitatively and quantitatively. Improvement of creative thinking abilities and mathematical dispositions on selected student have increased. The result of this research showed there was a relationship between mathematical creative thinking ability and mathematical disposition.